(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Contemporary pedagogical approaches to language acquisition for young learners prioritize flexible and effective methods, with game-based instruction emerging as a particularly valuable and increasingly prevalent technique. This article examines several effective game-based strategies designed to comprehensively address various aspects of language development in young children.